2017
DOI: 10.1097/md.0000000000006563
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure capnoperitoneum reduces stress responses during pediatric laparoscopic high ligation of indirect inguinal hernia sac

Abstract: Background: We aimed to evaluate the effect of different capnoperitoneum pressures on stress responses in pediatric laparoscopic inguinal hernia repair.Methods: In this prospective randomized controlled study, 68 children with indirect inguinal hernia who underwent high ligation of hernia sac were randomly divided into 3 groups: high-pressure group (12 mm Hg, HP group, n = 26); low-pressure group (8 mm Hg, LP group, n = 20); open operation group (OP group, n = 22). Heart rate (HR), blood pressure, and end-tida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…No difference in short-term adverse events, such as bleeding or hematomas, surgical site infection, inguinal swelling, pneumonia, and urinary retention, was found between open vs laparoscopic hernia repairs in numerous studies focusing on postoperative complications. [ 7 , 8 , 11 13 ] In our study, postoperative problems were observed in 4 of 56 (7.1%) patients and complications were similar in both groups ( P = .7467). These comprised bleeding or hematomas, surgical site infection, and inguinal swelling.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…No difference in short-term adverse events, such as bleeding or hematomas, surgical site infection, inguinal swelling, pneumonia, and urinary retention, was found between open vs laparoscopic hernia repairs in numerous studies focusing on postoperative complications. [ 7 , 8 , 11 13 ] In our study, postoperative problems were observed in 4 of 56 (7.1%) patients and complications were similar in both groups ( P = .7467). These comprised bleeding or hematomas, surgical site infection, and inguinal swelling.…”
Section: Discussionsupporting
confidence: 54%
“…The reported high recurrence rate and long learning curve in literatures are among its disadvantages. [ 4 8 ] As a result, some surgeons are also in favor of open surgery. A 24-year study by Pogorelić et al [ 9 ] from Japan found that Marcy hernia repair is a safe and effective procedure for inguinal hernia in children with excellent outcomes and a low incidence of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…For the in vivo experiments, the pneumoperitoneum pressure was set at 8 mm of Hg, since it is well known that an intra-abdominal pressure of 12 mmHg is poorly tolerated in rats [33, 34]. Preliminary results showed excellent tolerance of both PIPAC and electrostatic precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the incidence of postoperative delirium and cognitive dysfunction may be related to the in ammatory response of the central nervous system [15,16]. Reducing IAP and P a CO 2 could reverse this adverse effect [3]. Trendelenburg position could aggravate the mentioned adverse effect and change the intracranial hemodynamics subsequently increased intracranial pressure.…”
Section: Resultsmentioning
confidence: 99%
“…CO 2 pneumoperitoneum can promote the in ammatory response during surgery [2], which affects the patient's outcomes. At the same time, this effect varies with the change of intra-abdominal pressure(IAP) [3]. RALRP is similar to LRP, but the difference between the two procedures is that RALRP uses a computer to precisely control the robotic arm, the operation is more accurate and precise, and it can provide a better surgical eld of vision and three-dimensional anatomical structure for the surgeon.…”
Section: Introductionmentioning
confidence: 99%